Analysis of Corporate Governance Mechanisms, Financial Performance on Firm Value with Earnings Quality as Moderating Variable - Ika Kristanti (Jurnal Akuntansi Keuangan dan Bisnis, 2021)
This study aims to analyze the effect of corporate governance mechanisms, financial performance on firm value with earnings quality as a moderating variable. This study uses purposive sampling which obtained 48 samples of companies listed on the Jakarta Islamic Index for the period 2017 – 2019. The test results in the Inmek research prove that institutional ownership has no effect on firm value, managerial ownership does not affect firm value, independent commissioners affect firm value , financial performance has no effect on firm value, earnings quality is not able to moderate the relationship between institutional ownership, managerial ownership, independent commissioners and financial performance on firm value.